Application of Parking Retribution Income Forecasting at PT Bumi Daya Plaza Bengkulu City Using Trend Method Non Linear Squadratic Model - Fido Rama Nugraha; Jusuf Wahyudi; Arius Satoni Kurniawansyah (Penerbit Jurnal Indonesia, 2022)
The calculation of parking retribution income which has been managed by PT. Bumi Daya Plaza Bengkulu City used Microsoft Excel application. Data processing is only limited to revenue recapitulation. Then a forecasting application will be made that will be used to forecast future income, for the benefit of the company by using Trend Method Non-Linear Quadratic Model. Trend Method NonLinear Quadratic Model is a trend in which the value of the dependent variable increases or decreases linearly or a parabola occurs when the data is made a scatter plot (the relationship between the dependent and independent variables is quadratic) tend to be in one direction (up or down), such trends generally include movements lasting about 10 periods or more. This motion reflects the nature of continuity or a continuous state from time to time over a certain period of time, because of the nature of this continuity, the trend is considered a stable motion so that in interpreting it a mathematical model can be used, according to the circumstances and the time series data itself. Trend can be a straight line (regression/linear trend) or non-straight (regression/non-linear trend). The results obtained are derived from the processing of income for the last 12 months using Trend Method Non-Linear Quadratic Model. With data that has been processed from January 2020 to December 2020, it produces income forecasting at the T001 parking point of Rp. 467,272 and at the T002 parking point of Rp. 15,814,697 in January 2021. By using Trend Method Non-Linear Quadratic Model can determine forecasting/ prediction of parking retribution income in the future using preexisting data.